2017
DOI: 10.1101/144022
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FGF4retrogene on CFA12 is responsible for chondrodystrophy and intervertebral disc disease in dogs

Abstract: Chondrodystrophy in dogs isVariation in domestic dog (Canis familiaris, CFA) morphology has long fascinated both scientists and pet owners. Domestication of the dog from the wolf and the subsequent variation in size and shape within purebred dog breeds is a remarkable feat of animal breeding and selection. One of the most extreme examples of dog breed differences is in limb length, as extremely short limbs define many breeds. This morphological feature is present in breeds from all over the world and from all … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…5). We found that GFrelated signaling pathways were involved in the crosstalk network, mainly including the previously reported FGF family, 143,146 TGF-β family, 147,148 BMP family, 149,150 and PDGF family. 151 Among them, TGF-β was important due to the high activation of SMAD3 in NPPCs.…”
Section: Discussionmentioning
confidence: 72%
“…5). We found that GFrelated signaling pathways were involved in the crosstalk network, mainly including the previously reported FGF family, 143,146 TGF-β family, 147,148 BMP family, 149,150 and PDGF family. 151 Among them, TGF-β was important due to the high activation of SMAD3 in NPPCs.…”
Section: Discussionmentioning
confidence: 72%
“…2d). Of the seventeen autosomal QTLs that have been previously associated with body size (5,8,1422,25), only one (CFA3:62) did not reach significance using the imputed panel (significance threshold of P = 1×10 −8 ), with P -values of 1.1×10 −5 , 2.1×10 −7 and 1.8×10 −8 for individual weight, breed-average weight and breed-average height respectively (S2 Table). GWAS of breed-average weight provided the most power on average, so we will focus on that phenotype for the rest of the body size analyses.…”
Section: Resultsmentioning
confidence: 99%
“…It is also highly prevalent within the French Bulldog, Dachshund, Beagle and Cocker Spaniel breeds, who are all associated with intervertebral disc herniation. 15 The combination of these two genetic findings may help in part to explain the incidence of IVDH in the French Bulldog breed. 12 Specifically, the DVL2 gene through its contribution to the formation of French Bulldogs screw tail and thoracic CVM, and the possible destabilizing spinal effects this causes, in conjunction with increased rate of disc degeneration caused by the FGF4 gene.…”
Section: Discussionmentioning
confidence: 99%
“…1,9,[12][13][14] However there is also a genetic association between chondrodystrophy and accelerated disc degeneration in the French Bulldog due to the FGF4 retrogene. 15,16 The role of genetics in the development of CVM has also been investigated with genomic sequencing finding a link between the presence of screw tails and thoracic vertebral malformations in the Bulldog breeds due to a frameshift mutation in the Disheveled 2 (DVL2) gene. 17 The majority of research into the significance of CVM in these breeds is based on European populations of dogs.…”
mentioning
confidence: 99%